Korelasi Iklim Kerja Dengan Kecelakaan Kerja Di PT. Japfa Comfeed Indonesia TBK Bati-Bati Kalimantan Selatan - Alfina Inayah; Tien Zubaidah; Maharso Maharso; Noraida Noraida (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2016)
Abstract: Correlation of Work Climate With Occupational Accidents At PT Japfa Comfeed Indonesia Tbk Bati-Bati South Kalimantan. One of the working conditions that can cause health problems for workers is exposure to heat. Climate improper work may cause health problems and lead to impaired concentration of labor that resulted in accidents. This study aim to determine the relationship work climate with occupational accidents in animal feed production process unit in PT Japfa Comfeed Indonesia Tbk Bati-bati on Jl. A. Yani Km 35,5 Desa Nusa Indah Bati-Bati, Tanah Laut, South Kalimantan. Cross sectional study design with a total population of 30 labors and samples selected by total sampling were analyzed using Chi-Square test. The results showed that the working environment at the 1st floor 28,69oC , on the 2nd floor 28,90oC and 3rd floor 30,50oC which means that the working climate on the 3rd floor exceeds NAB. Occupational accidents occurred on the 1st floor of  25% , the 2nd floor of 14,3 % and 3rd floor of to 63,6 %. From the results of the bivariate analysis using Chi-square test proved to be statistically significant relationship between work climate with the accident in unit production PT Japfa Comfeed Indonesia Tbk Bati-Bati. Efforts should be made to address the working environment exceeds the NAB is with improved ventilation and the provision of drinking water that meets the needs of labor and provision of clothes that absorb sweat like cotton. Keywords: Work Climate; Occupational Accidents; PT Japfa Comfeed Indonesia Tbk